AUTOMATED MUSIC COMPOSING WITH NORMAL RANDOM NUMBERS DISTRIBUTION AS “INFORMATIONAL DNA” SEQUENCING - Vishnevsky, Oleksandr Volodymyrovych (Science-based technologies, 2019)
There are approximately 3 billion of the base pairs in a human genome, a complete set of deoxyribonucleic acid (DNA), made of two twisting paired strands, consists of four nucleotide bases - adenine (A), thymine (T), guanine (G) and cytosine (C). At the same time chromatic musical scale consists of twelve pitches, forming a 12-tone equal temperament, which is today a most often used temperament in Western music. It is clear that one can interpret these 12 tones sequence as a sort of “informational DNA nucleotides” sequence. It’s an approach, that can change music perception for a listener and can help to compose a more cognitive, conceptual music for a composer. Biotechnical automated control system (BACS) for music composing helps the composer to produce music with less effort, and because of it to pay more attention to the nuances, and at the same time to general quality of composed music. The generalized structural scheme of BACS consists of three main building blocks: A –neural network based software “Aquarius”; C – a human composer himself; L – a listener, or a patient of music therapy impact. All three components are inseparable, C and A elements create mutual dependence, because they interact all the time in the process of music creation. They also impact the L element, because this element is undoubtedly the BACS object of impact. The random musical signal is being created with the help of standard rand() and srand() C++ functions. In the BACS “Aquarius” to this day only uniformly distributed random numbers were used. But in order to improve performance, to widen the opportunities for choosing the needed tools for a musical composition, it is possible, of course, to introduce different distributions, such as normal, Poisson, exponential, Weibull, lognormal, discrete, piecewise constant, piecewise linear etc. The c++ code for normal distribution allows to generate random numbers, managed by two main parameters – mean and standard deviation. This code has been inserted into the main code and new stochastic music has been obtained with its assistance.